A influência do controlador gupfc no sistema elétrico de potência visando a estabilidade a pequenas perturbações - Valle, Danilo Basseto do [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This thesis proposes a power injection model for the GUPFC (Generalized Power Flow Controller) which is suited for the GUPFC representation in both power flows and optimal power flows analyses. It is also proposed a model for the control system GUPFC that represents its dynamics in electric power systems. This work main aim is the small signal stability analysis. However, the power injection model of the GUPFC and the structure control model could be used in nonlinear environment. The algebraic equations provided by the power injection model of the GUPFC and the dynamical equations obtained from the control model, are used to analyze the influence of the GUPFC on the system, initially executing a static approach (in steady state) using the expanded power flow tools. The expanded power flow considers the differential variables as algebraic, at a given equilibrium point, and the problem is to find the zeros of a nonlinear function set, whose solution can be obtained by a Newton Raphson method as in a conventional power flow. From the solution of the power flow, it is possible to include directly the corresponding sub matrices of the GUPFC in to the Power Sensitive Model (PSM), which is the chosen model to represent all the dynamic components of the system. Once, every component is modeled in the PSM, a small signal stability is performed. The ESP and POD controllers are included in to the control loop of the Automatic Voltage Regulators (AVR) and the GUPFC respectively, to improve the dynamical performance of the system. To provide additional damping to the unstable or little damped modes and increase the stability limits, a Particle Swarm Optimization (PSO) technique is used to provide the parameters of the supplementary damping controller. Two objective functions are proposed to lead the problem solution to good results and then compared to well known classical techniques

Neste trabalho é proposto um modelo de injeção de potência para o controlador Generalized Unified Power Flow Controller (GUPFC) que permite representá-lo em programas de fluxo de potência e fluxo de potência ótimo. Também é proposto um modelo para a estrutura do sistema de controle do GUPFC que permite representar sua dinâmica em sistemas elétricos de potência. Todas as análises dinâmicas realizadas neste trabalho visam a estabilidade a pequenas perturbações, porém, o modelo de injeção de potência do GUPFC e o modelo de sua estrutura de controle permitem representálo também em um ambiente não linear. A partir das equações algébricas fornecidas pelo modelo de injeção de potência do GUPFC e das equações dinâmicas obtidas a partir da sua estrutura do sistema de controle, é possível analisar a influência que o controlador GUPFC causa no sistema, realizando-se inicialmente uma abordagem estática (em regime permanente), que foi realizada utilizando-se a ferramenta de fluxo de potência expandido. A ferramenta de fluxo de potência expandido trata as variáveis diferenciais como algébricas, para um dado ponto de equilíbrio, ficando o problema restrito a encontrar os zeros de um conjunto de funções não-lineares, cuja solução pode ser obtida através do método de Newton-Raphson, como em um fluxo de potência convencional. Com a solução desse fluxo de potência, pode-se incluir diretamente as correspondentes submatrizes do GUPFC no Modelo de Sensibilidade de Potência (MSP), já que este foi o modelo escolhido para representação de todos os componentes dinâmicos do sistema. Com todos os componentes modelados no MSP, foi realizada uma análise dinâmica do sistema, visando a estabilidade a pequenas perturbações. Para melhorar o desempenho dinâmico do sistema, foi essencial que controladores ESPs e POD fossem inclusos às malhas de controle dos Reguladores Automáticos ...
Keywords: Controle automatico; Automação; Automatic control